THE MAIN CAUSES OF THE DEVELOPMENT OF PEPTIC ULCER OF THE STOMACH AND DUODENUM (American Journal of Interdisciplinary Research and Development, 2025)
In recent years, there has been an increase in the incidence of duodenal ulcer and an increase in the number of complicated forms. Bleeding from duodenal ulcers is the most formidable complication and occupies one of the first places in the structure of mortality from duodenal ulcer. The anamnestic, clinical features and pH values in children with duodenal ulcer were studied. The study allows us to consider sex, age, heredity, erosive nature of gastroduodenitis, multiple ulcers, high bacterial contamination, low pH in the antroduodenal zone as factors for the complicated course of duodenal ulcer.